ISLAM DAN AKULTURASI BUDAYA LOKAL DI ACEH (Studi Terhadap Ritual Rah Ulei di Kuburan dalam Masyarakat Pidie Aceh) - Muhammad Arifin; Khadijah Binti Mohd Khambali @ Hambali (Islam Futura, 2016)
The people of Aceh are known for adherence to religion and uphold the culture and customs. Before Islam came to Aceh, Hindu and Buddhist influence is rooted in the traditions and beliefs of Acehnese society. Therefore, even though Islam has flourished and developed in Aceh, there are some cultures and traditional beliefs which is still preserved by the people of Aceh. It is strongly associated with the teachings of Ahl al-Sunnah wa al-Jama'ah which is the only school of theology of the people of Aceh. The existence of those cultures and traditional beliefs leaded Islamic culture as a newcomer must be in harmony with. Consequently, there was a process of influencing each others. It formed a traditional Islam i.e., the Islam that has been acculturated to the culture and beliefs before. One of those traditional cultures which has been practiced in Aceh is rah ulei. This research aims at studying the cultural acculturation in Aceh i.e. rah ulei from the Islamic perspective. The data was obtained through interviews and observations, then analyzed by descriptive analysis method. The results show that there are some traditions and cultures of Aceh which acculturated with foreign culture, including rah ulei. Meanwhile, according to the Islamic perspective, worshiping grave or asking divine spirits for something but God is violating Islamic theology.